Chronic low BPS exposure through diet impairs in vitro embryo production parameters according to metabolic status in the ewe - Alice Desmarchais; Ophélie Téteau; Nathalie Kasal-Hoc; Juliette Cognié; Olivier Lasserre; Pascal Papillier; Marlène Lacroix; Claire Vignault; Peggy Jarrier-Gaillard; Virginie Maillard; Aurélien Binet; Maria-Teresa Pellicer-Rubio; et al. (Ecotoxicology and Environmental Safety, 2022)
Bisphenol A (BPA), an endocrine disruptor, has been replaced by structural analogues including bisphenol S (BPS). BPA and BPS exhibited similar effects regarding reproductive functions. Moreover, metabolic status and lipid metabolism are related to female fertility and could worsen BPS effects. The objective was to determine BPS in vivo effects on folliculogenesis and embryo production after chronic exposure through diet, and the influence of metabolic status in adult ewes. Sixty primiparous 2.5 year-old ewes, undergoing a restricted or well fed diet, were exposed to BPS (0, 4 or 50 µg/kg/day) for at least three months. After hormonal oestrus synchronisation and ovarian stimulation, ewes were subjected to ovum pick-up (OPU) procedures to collect immature oocytes, that underwent in vitro maturation, fertilisation and embryo production. Body weight, body condition score and plasma glucose were higher in well-fed compared to restricted ewes, while plasma NEFA was lower during the 4–5 months after the beginning of the diets. Plasma progesterone levels increased on day 5 before OPU session in well-fed compared to restricted ewes. No effect of BPS dose was observed on follicle population, plasma AMH levels and embryo production numbers and rates. However, a significant diet x BPS dose interaction was reported for cleaved embryos, > 4-cell embryos, blastocyst and early blastocyst numbers, and plasma triiodothyronine levels. Our study showed that a contrasted diet did not affect follicle population nor embryo production in adult ewes but could affect the quality and progesterone secretion of the corpus luteum. Chronic low BPS exposure had no effect on follicular population and oocyte competence. Nevertheless, the significant diet x dose interactions observed on embryo production suggest that BPS effect is modulated by metabolic status. Further studies are required to assess the risk of BPS exposure for public reproductive health.